2021
DOI: 10.1088/1755-1315/774/1/012114
|View full text |Cite
|
Sign up to set email alerts
|

Shear and vortex instabilities at deep part load of hydraulic turbines and their numerical prediction

Abstract: For all types of turbines, deep part load operation (DPL) poses a challenge. An example of a dynamic phenomenon due to vaneless space vortices occurring at DPL is presented for three turbine types: a diagonal, a propeller and a Francis turbine. The backflow region occurring at DPL is often considered to be a main factor in these phenomena. Our results confirm that these backflow regions play an important role, but other factors also seem to be significant in specific cases. In our example of a diagonal turbine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
3
6
0
Order By: Relevance
“…20 Several researchers concluded that the flow at SNL is mainly stochastic, 10,[20][21][22][23][24][25][26][27][28] while others found that this condition also presents periodic phenomena, such as vaneless space vortex (VSV) structures which consist of a certain number of vortices rotating at a fixed frequency. [29][30][31][32][33][34][35][36][37] On the one hand, Melot et al 24 and Nennemann et al 23 performed numerical fatigue calculations on Francis runners working at SNL and found that most of the fatigue damage inflicted on the runner blades was induced by stochastic flow phenomena. On the other hand, Nennemann et al 37 studied, numerically and experimentally, the VSV structures occurring at deep part load (DPL) and SNL on a diagonal turbine, a propeller, and a Francis turbine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Several researchers concluded that the flow at SNL is mainly stochastic, 10,[20][21][22][23][24][25][26][27][28] while others found that this condition also presents periodic phenomena, such as vaneless space vortex (VSV) structures which consist of a certain number of vortices rotating at a fixed frequency. [29][30][31][32][33][34][35][36][37] On the one hand, Melot et al 24 and Nennemann et al 23 performed numerical fatigue calculations on Francis runners working at SNL and found that most of the fatigue damage inflicted on the runner blades was induced by stochastic flow phenomena. On the other hand, Nennemann et al 37 studied, numerically and experimentally, the VSV structures occurring at deep part load (DPL) and SNL on a diagonal turbine, a propeller, and a Francis turbine.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37] On the one hand, Melot et al 24 and Nennemann et al 23 performed numerical fatigue calculations on Francis runners working at SNL and found that most of the fatigue damage inflicted on the runner blades was induced by stochastic flow phenomena. On the other hand, Nennemann et al 37 studied, numerically and experimentally, the VSV structures occurring at deep part load (DPL) and SNL on a diagonal turbine, a propeller, and a Francis turbine. The backflow region was found to play a key role in their formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In axial turbines, SNL operation also presents stochastic flow phenomena and coherent vortex structures, which are usually originated in the vaneless space and cause low-frequency pressure fluctuations and significant vibrations [21][22][23][24][25][26][27][28][29][30][31][32][33]. Yang et al [21] investigated numerically the origin of strong pressure fluctuations and vibrations in an axial turbine operated at SNL.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to inter blade vortices, axial runners may also be afflicted by other types of vortices occurring in the vaneless space between guide vanes and runner blades. Those vaneless space vortices have been described hydraulically in previous publications [4]- [7] but attempts to predict dynamic stresses under their influence has not yet been done. This study presents strain gauge measurements on a fixed-blade axial prototype runner.…”
Section: Introductionmentioning
confidence: 99%